Answer:
x = (-5)/3
Explanation:
Solve for x:
19 - 6 x = 29
Hint: | Isolate terms with x to the left hand side.
Subtract 19 from both sides:
(19 - 19) - 6 x = 29 - 19
Hint: | Look for the difference of two identical terms.
19 - 19 = 0:
-6 x = 29 - 19
Hint: | Evaluate 29 - 19.
29 - 19 = 10:
-6 x = 10
Hint: | Divide both sides by a constant to simplify the equation.
Divide both sides of -6 x = 10 by -6:
(-6 x)/(-6) = 10/(-6)
Hint: | Any nonzero number divided by itself is one.
(-6)/(-6) = 1:
x = 10/(-6)
Hint: | Reduce 10/(-6) to lowest terms. Start by finding the GCD of 10 and -6.
The gcd of 10 and -6 is 2, so 10/(-6) = (2×5)/(2 (-3)) = 2/2×5/(-3) = 5/(-3):
x = 5/(-3)
Hint: | Simplify the sign of 5/(-3).
Multiply numerator and denominator of 5/(-3) by -1:
Answer: x = (-5)/3